(The Study on Use of Nonleaves and Tea Leaves as Functional Drinks) - Solechan -; Enny Hawani Lubis; Dede Abdurahman (Balai Besar Industri Agro, 2006)
Study on the use of functional tea made of nony (Morinda citrifolia)and tea (Camellia sinensis)leaves as functional drink had been conducted.The objective of this study is to obtain the best formula in producing in the most preferred drink.The study was conducted by making dried tea of nony and green tea leaves,followed by formulation step to produce ready to drink products in cup packaging.The composition ready drink product consist of dried nony leaves (100%) dried green tea leaves (100%) and mixture of dried nony and green tea leaves (1:1,1:2,2:1),with addition of sugar(13%),citric acid (0,5,1,0 and 1,5%),honey (2.0,4.0,and 6.0%),salt(0.01%)and addition of lychee,strawberry,and orange flavors.The sensory test showed that the best formulation was the mixtured of nony and green tea (1:1),contents of sugar 13%,citric acid was 0,5%,salt was 0.01%and small amount of strawbeery flavor.While chemical and microbiologycal analysis showed that it was in conformity with requirements in SNI 01-3143-1993 concerning tea drink in pack.Value of pH ranged between 3,52-3,66,sugar content was between 12,89-13,36% and TPC was smaller than 10 colonies/ml.Products kept storage for 8 weeks were still in good addition.